Analysis of Factors Influencing Microstructure and Mechanical Properties of Austempered Ductile Iron - Vasko, Alan (Communications - Scientific letters of the University of Zilina, 2009)
The paper deals with some factors influencing microstructure and mechanical properties of austempered ductile iron (ADI). Final structure and properties of ADI are obtained by exactly controlled process of heat treatment of nodular cast iron. The influence of conditions of isothermal heat treatment on microstructure and mechanical properties of austempered ductile iron, especially different temperature of isothermal transformation of austenite and different holding time at this temperature, is shown in the paper.